Diverse Transformations of Chiral Propargylic Alcohols Generated by BINOL-Catalyzed Alkyne Addition to Aldehydes - Wang, Qin; Pu, Lin (Synlett, 2013)
Asymmetric alkyne addition to aldehydes catalyzed by our BINOL-based (BINOL = 1,1′-bi-2-naphthol) catalyst system has allowed easy access to a variety of functionalized chiral propargylic alcohols with high enantiomeric purity. This article summarizes our work on using these chiral propargylic alcohols for the synthesis of structurally diverse organic molecules.Optically active tetronic acids and aminofuranones have been synthesized by the regiospecific hydration and amine addition, respectively, of chiral γ-hydroxy-α,β-acetylenic esters, a type of functionalized propargylic alcohol. Ruthenium–carbene-catalyzed ring-closing metathesis and octacarbonyldicobalt(0)-mediated Pauson–Khand (PK) cycloadditions have been used to convert propargylic alcohol based enynes into optically active mono- and bicyclic products, respectively. A chiral propargylic alcohol derived dienediyne has been subjected to a rhodium(I)-catalyzed PK cycloaddition, followed by enyne metathesis catalyzed by the Grubbs II catalyst and a Diels–Alder reaction, leading to the formation of a polycyclic product with high chemo- and stereoselectivity. Finally, a highly chemo- and stereoselective domino PK/[4+2] cycloaddition of a series of optically active trienynes has been discovered to quickly generate tetracyclic products that contain a spirocyclic framework and a quaternary carbon center.This work demonstrates that the BINOL-catalyzed asymmetric addition of alkynes to aldehydes is a very useful process for the asymmetric synthesis of structurally diverse organic products.1 Introduction2 Conversion of γ-Hydroxy-α,β-acetylenic Esters2.1 Conversion into Tetronic Acids2.2 Conversion into Aminofuranones2.3 Conversion into γ-Acetoxy-Substituted Dienoates3 Conversion of Chiral Propargylic Alcohol Based Enynes3.1 Conversion into Cycloalkenes by Ring-Closing Metathesis3.2 Conversion into Bicyclic Products by Intramolecular Pauson–Khand Cycloaddition3.2.1 Using Chiral Enynes Derived from Pent-4-enal To Generate Fused 5,5-Bicyclic Products3.2.2 Using Chiral Enynes Derived from Hex-5-enal To Generate Fused 6,5-Bicyclic Products3.2.3 Using Chiral Allyl Propargyl Ethers for the Pauson–Khand Reaction3.2.4 Discussion about the Stereoselectivity of the Intramolecular Pauson–Khand Reaction 4 Conversion of Chiral Propargylic Alcohol Based Enediynes4.1 Preparation of Optically Active Dienediynes and Their Conversion into Bicyclic Products Using the Pauson–Khand Reaction4.2 Ring-Closing Metathesis To Construct 5,5,7- and 5,5,8-Tricyclic Compounds4.3 Using the Highly Diastereoselective Diels–Alder Reaction To Construct a Fused 5,5,7,6-Polycyclic Compound4.4 Reversing the Diastereoselectivity of the Rhodium(I)-Catalyzed Pauson–Khand Cycloaddition of Chiral Enediynes5 Conversion of Chiral Propargylic Alcohol Based Trienynes5.1 Domino Pauson–Khand/[4+2] Cycloaddition of Optically Active Trienynes in the Presence of [RhCl(CO)2]25.2 Proposed Mechanistic Explanation for the Chemo- and Stereoselectivity of the Domino Pauson–Khand/[4+2] Cycloadditions5.3 Related Catalytic Conversion of a Chiral Dienediyne in the Presence of [RhCl(CO)2]26 Summary
Keywords: propargylic alcohols; asymmetric synthesis; Pauson–Khand cycloaddition; ring-closing metathesis; polycycles